Learning Fairy Tales Using E-Modules Assisted by Illustration Images for Grade VI Elemantary School Students - Anastasia Titin Rosnawati; Kuntoro Kuntoro (UM Purwokerto Press, 2023)
This study aims to see that the use of e-modules in learning fairy tales can be used as an alternative teaching material in 21st century learning. Where 21st century learning presents a learning process that pays attention to the steps of discovery and concept development independently by students. The type of data used in this research is secondary data. The method used in this study is a qualitative description. The data obtained is compiled, analyzed, and concluded to get conclusions about the literature study. Based on the research results, students want learning to use interesting media. The use of interesting learning media makes learning more fun. The use of e-modules assisted by illustrations on fairy tale material is effectively used in learning.